Social Exchange Process in Ecotourism: Realizing Benefits for the Local Community - Ali, Md. Borak (Curtin University, 2017)
This study addresses the exchange relationships among ecotourism stakeholders in Bangladesh. A mix-method research design of QUAL-QUAN is adopted for this research. On the theoretical side social exchange theory is blended with the theory of planned behaviour to study the impact of various social exchange relationships and community’s attitude and behaviour on improved standard of living due to ecotourism. Findings indicate that community intention and participation in ecotourism improves standard of living in ecotourism destinations.